The red badge of courage [large type] - Crane, Stephen, 1871-1900 (Kennebec Large Print perennial favorites collection., 2010)
With no idea of the horrors of war, young Henry Fleming has romantic notions of the hero he will be. Those illusions are destroyed when he enters his first battle. Now he must make the most difficult decision of his life: run or fight.